78-Year-Old Female With Left Hip Fracture: Palliative Medicine in the Emergency Department Simulation Case - Haleh Van Vliet; Ryan Thompson; Joshua Ross (Association of American Medical Colleges, 2015)
Abstract Palliative medicine has been identified as the new frontier in emergency medicine (EM). For many, the union of these two fields is counterintuitive. However, it is not uncommon for terminally ill patients either actively contemplating or already enrolled in hospice to present to the Emergency Department (ED). Thus, it is essential that ED providers develop the skills to appropriately care for this patient demographic. Given the unfamiliarity of this territory, simulation offers a protected environment for both learners and educators to launch training endeavors. This case is based on actual patient encounters at the University of Wisconsin Hospital and Clinics (UWHC). The case is that of a complicated geriatric patient with metastatic cancer who presents with a left hip fracture in the setting of a fall; the patient progressively decompensates while in the ED due to an acute massive pulmonary embolism. As part of an intradepartmental simulation contest, the case was presented to two separate teams of EM faculty members as a formative assessment. Residents and other faculty members observed either team complete the 10− to 15-minute case via video monitoring and then voted to determine which team advanced to the final round of simulation. Another period of 20-30 minutes was allotted for debriefing. The effectiveness of this simulation case in meeting the educational objectives was gathered in the context of the entire simulation series, which included feedback from both simulation participants and simulation observers. The simulation case presented here created a unique opportunity to engage both EM residents and faculty at the UWHC in the practice of basic palliative medicine skills.